The evolution of a dialogue-centered intercultural education – the tool for social inclusion - Spajić-Vrkaš, Vedrana (2012)
In this paper we argue that intercultural dialogue has been established as a concept and an educational strategy in theoretical and political discourses only recently as answer to a long-lasting challenge of accommodating to the culturally different. It is seen, especially in Europe, as a crucial tool for promoting social inclusion in a post-assimilation era, which is characterized by deep changes in the normative conceptualization of citizenship, by the recognition of cultural difference as social strength and by an understanding that the viability of culturally complex societies largely depends on how we learn the society’s culture(s) through education. In order to explain our position, the following issues are discussed: what is intercultural dialogue and how does it contribute to social inclusion ; why has it been recognized as the key tool for the transformation of culturally plural societies into inclusive societies only recently ; why have earlier approaches to intercultural/multicultural education, despite their optimistic claims, actually failed to promote intercultural dialogue and thus to contribute to social inclusion and, finally, how a dialogue-centered inclusive intercultural/multicultural education may be promoted in schools. In particular, we claim that the evolution of a dialogue-centered intercultural/multicultural education should be understood in relation to the process of recognition and promotion of cultural pluralism as a socially formative principle. This process is explained through four interrelated stages: the Golden Ages of Ignorance, the Disturbing Ages of (political) Rhetoric, the Promising Ages of Accommodation, and the Challenging Ages of Exchange. Education became a tool for the transmission of cultural pluralism in the second stage but it did not contribute significantly to the consolidation of the culturally complex societies due to its reliance on a mono-cultural perspective in which the differences were seen as a transitional social feature, i.e., as an anomaly that was expected to ‘naturally’ vanish in the course of time. This is the reason why the first multicultural/intercultural education programs targeted solely the culturally different students for the assimilation purpose. This approach was soon replaced by a multicultural perspective in which cultural differences began to be thought of as social reality, i.e., as something that is ‘there to stay’. Consequently, education shifted from the minority to all the students with an aim to fight their ethnocentrism, stereotypes and prejudices but without altering the structure of school or the society. The intercultural perspective emerged in 1993 at the First European Summit at which it was declared that cultural differences were to be seen as the society’s strength (“Europe as unity in diversity”). Some 15 years later intercultural dialogue became the key to promoting that strength through intercultural education. Following the analysis of the impact of these perspectives on education, we conclude in the end that neither dialogue-centered intercultural education would contribute to social inclusion if the dialogue were not based on the principles of human rights, equality and social justice, which is why we term the most recent stage of the promotion of cultural pluralism - the Challenging Ages of Exchange.
ENG